On the fatigue behaviour of quenched and tempered at 300 and 600 °C SAE 1045 steel in an environment of sugar cane juice. Issue 10 (8th April 2016) - Muñoz Cubillos, J.; Rodríguez, S.A.; Coronado, J.J.
Abstract: SAE 1045 steel is widely used for manufacturing shafts in the sugar cane mills of the sugar industry. These shafts are designed with an expectation of a long lifetime. However, fatigue failures occur frequently. The sugar cane juice processed in these mills has corrosive properties that can alter the fatigue life of these shafts. In this research, the fatigue strength of SAE 1045 steel between 1 × 10 4 and 2 × 10 5 cycles in air and in sugar cane juice, with two different microstructures (tempered martensite at 300 °C and tempered martensite at 600 °C), was determined in rotating bending. The microstructure of the materials was characterized using optical microscopy, and the fracture surfaces were characterized using scanning electron microscopy. The results show that the fatigue strength at 2 × 10 5 cycles for the tempered condition at 600 °C decreases 7% because of the sugar cane juice effect, and for the tempered condition at 300 °C, the fatigue strength decreases 15%.